AN ASSESSMENT OF LABOUR DAILY WAGE RATE FOR AGRICULTURAL PRODUCTION ACTIVITIES IN THE NORTH CENTRAL ZONE, NIGERIA - Akintobi, Olarenwaju S.; Ajah, Julius; Edu, Edwin E. (FUDMA Journal of Sciences, 2021)
The study evaluated small-scale farmers’ access to human labour in North Central Nigeria. Multi-stage random sampling technique was used for sample selection while questionnaires were used for data collection. A total of 1,750 farmers were randomly interviewed. Data were analyzed using descriptive statistics and two-way mixed factorial analysis of variance and mean separation was done at 5% probability level. Result revealed labour wage per rate significantly (P < 0.05) dependent on the labour category, the location (state) and the effect of both human labour type and location (state). Mean separation showed adult male is the highest paid while young female is the least paid, while Kwara State has the highest labour wage rate and plateau State has the lowest wage rate per day. Based on the findings, the research concluded that small scale farmers access to labour based on wage rate is low, cost of agricultural labour is high which has resulted increased cost of production for the small-scale farmers. The study recommends among others that combine hiring should be encouraged among farmers for the adoption of expensive labour saving technologies/ implements
Keywords: Small Scale farmers, labour, Access, Wage rate